Jesus’ Political Involvement and Its implications to the Church in Kenya - Kinoti, Mary (International Journal of Professional Practice, 2022)
Christ’s political involvement throughout His life on earth and in His ministry is a model example for the Church in Kenya to emulate in their endeavour to influence the politics of the day. Jesus was affected by the politics of His day right from his birth up to His ministry later on. In his ministry, Jesus Christ healed the sick, fed the hungry, delivered the oppressed and challenged those in political power. The study aimed to examine how Jesus was involved in politics of his day; to investigate the place of the church in politics; and to determine whether the modern day church is following the example of Jesus Christ in its involvement in politics. The study examined secondary data from the library sources. Primary data was collected from 40 senior ordained clergy purposively selected from the Methodist church in Kenya. They comprised superintendent Ministers and Bishops. The data was collected through open ended questionnaires and interviews. Data analysis process involved mixed method approaches, where it was analyzed both qualitatively and quantitatively. Qualitative data was analyzed through themes and patterns, while quantitative data was analyzed through the statistical package for the social sciences (SPSS) version 23 for descriptive statistics such as frequency distributions and percentages. The data obtained was grouped in themes consistent to the study objectives, analysed and conclusions made. The study concluded that there is a close relationship between the church and politics. The study recommends that the Church in Kenya becomes more deliberate in its engagement in politics by emulating Jesus Christ who is the model. Further, the Church needs to be prepared to be persecuted and crucified by the political class just like Christ was.